Inorganic oxide particles
By adjusting the particle size distribution and shape characteristics of inorganic oxide particles, the problem of insufficient fluidity and density balance of powder material in the adhesive jet laminated shape is solved, and the uniform laying and low shrinkage of the three-dimensional laminated shape is achieved.
Patent Information
- Application Number
- CN202380040490.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-26
- Filing Date
- 2023-12-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the adhesive jet lamination molding technology, the existing inorganic oxide powder material lacks fluidity and density balance, resulting in uneven distribution of voids and materials in the three-dimensional lamination molding body, and the shrinkage rate during sintering is relatively high. .
Inorganic oxide particles with D50 of 5.5 to 9.0 μm and roundness of 0.90 or above are adopted to ensure uniform laying and high-density filling of the powder layer by adjusting the particle size distribution and shape characteristics, and maintain shape stability during the sintering process and reduce shrinkage. Rate.
The moderate fluidity and high volume density of inorganic oxide powder are achieved, ensuring that the adhesive enters the powder material evenly, reducing the shrinkage rate during sintering, and improving the density and shape stability of the three-dimensional layered molding body.
Smart Images

Figure BDA0005134351340000101 
Figure BDA0005134351340000111 
Figure BDA0005134351340000121
Abstract
Description
Technical Field
[0001] The present disclosure relates to inorganic oxide particles, a sintered body thereof, and a method for producing a binder spray-type laminated body. Background Art
[0002] In recent years, processing methods such as additive manufacturing (AM) technology and 3D printing technology have attracted attention. This is a technology that produces a cross-sectional shape based on the data of the three-dimensional shape of the target body and stacks it to obtain the target body. As additive manufacturing technology, there are known processing methods such as: a binder jet method that selectively shapes by spraying a binder onto a powder material on a modeling table (Patent Document 1); a material jet method that selectively shapes by spraying a photocurable resin from an inkjet nozzle; a powder bed melting method that selectively melts a powder bed covered with metal powder or the like by irradiating it with a laser or electron beam; and a photoforming method (Patent Document 2) that shapes a slurry obtained by mixing a liquid photocurable resin and an inorganic powder by irradiating light.
[0003] Prior Art Literature
[0004] Patent Document 1: Japanese Patent Application Publication No. 2016-117069
[0005] Patent Document 2: Japanese Patent Application Publication No. 2021-11050 Summary of the invention
[0006] The binder jetting method is also known by the term "3D inkjet powder printing". This method includes, for example, a process of supplying a powder material to a molding table using a roller to form a uniform powder layer; and a process of applying a liquid binder to the powder layer through an inkjet print head to selectively combine a part of the powder layer. By repeatedly performing these processes, a three-dimensional stacked molding body as the target can be obtained. Thereafter, the three-dimensional stacked molding body is sintered as required. In the binder jetting method, a structure in which the constituent materials are unevenly distributed, such as voids, is sometimes generated in the obtained three-dimensional stacked molding body. In order to suppress this situation, it is desired that the stacked molding powder has good laying properties that can be smoothly supplied to the molding table and can be evenly spread. In addition, it is believed that by filling the stacked molding powder with a high density, a three-dimensional stacked molding body with high uniformity can be obtained. In order to achieve good laying properties and high-density filling, it is useful to improve the fluidity of the powder material. On the other hand, when applying the binder, it is also required that the powder layer is not disturbed and the binder can enter between the powder materials. In addition, it is also desired that the shrinkage rate during sintering is low.
[0007] The present disclosure provides an inorganic oxide particle which, when used as a powder for stacked modeling, has moderate fluidity, good laying properties capable of forming a uniform powder layer and shape stability capable of maintaining a shape from the application of an adhesive to a sintering process, and also has a moderate bulk density, which enables the adhesive to enter between powder materials and achieve a low shrinkage rate during sintering.
[0008] The contents of this disclosure relate to the following matters.
[0009] [1] an inorganic oxide particle,
[0010] D50 is 5.5~9.0μm,
[0011] The pressure loss for air permeation at a pressure of 12 kPa is 1.75 to 2.81 kPa.
[0012] [2] The inorganic oxide particles according to [1], wherein (D10+D90) / D50 is 2.7 or more.
[0013] [3] The inorganic oxide particles according to [1] or [2], wherein the BET specific surface area is 0.10 to 10.00 m 2 / g.
[0014] [4] The inorganic oxide particles according to any one of [1] to [3], wherein the volume ratio of particles having a particle size of 16.8 to 60.0 μm is 4.3 to 33.5 volume %.
[0015] [5] The inorganic oxide particles according to any one of [1] to [4], wherein the volume ratio of particles having a particle size of 2.0 μm or more is 90.0% by volume or more.
[0016] [6] The inorganic oxide particles according to any one of [1] to [5], which are aluminum oxide.
[0017] [7] The inorganic oxide particles according to any one of [1] to [6], wherein the circularity is 0.90 or more.
[0018] [8] The inorganic oxide particles according to any one of [1] to [7], which are used in a powder layering method.
[0019] [9] The inorganic oxide particles according to [6], wherein the compacted bulk density at a pressure of 98 MPa is 2.45 to 2.54 g / cm 3 .
[0020]
[10] A sintered body, which is a sintered body of the inorganic oxide particles according to any one of [1] to [9].
[0021]
[11] A method for producing a three-dimensional layered structure by a binder spraying method, comprising: applying a liquid containing a binder to the inorganic oxide particles described in any one of [1] to [9] to form a three-dimensional layered structure.
[0022]
[12] A method for producing a sintered body, comprising:
[0023] Applying a liquid containing a binder to the inorganic oxide particles described in any one of [1] to [9] to form a three-dimensional layered structure; and
[0024] The three-dimensional stacked shaped body is sintered.
[0025] According to the present disclosure, an inorganic oxide particle can be provided which, when used as a powder for stacked modeling, has moderate fluidity, good laying properties capable of forming a uniform powder layer, and shape stability capable of maintaining the shape from the application of the binder to the sintering process, and also has a moderate bulk density, which enables the binder to enter between the powder materials and achieve a low shrinkage rate during sintering. DETAILED DESCRIPTION
[0026] Hereinafter, embodiments of the present invention will be described. Note that the embodiments described below are representative examples of the present invention and are not intended to limit the present invention.
[0027] In this specification, regarding a numerical range, when "~" is used, the values at both ends are the upper limit and the lower limit, respectively, and are included in the numerical range. When there are multiple upper limits or lower limits, a numerical range can be created based on all combinations of the upper limits and the lower limits. Similarly, when there are multiple numerical ranges, another numerical range can be created by individually selecting upper limits and lower limits from these numerical ranges and combining them.
[0028] In this specification, D10, D50 and D90 are the 10% particle size, 50% particle size and 90% particle size in the volume-based cumulative particle size distribution measured using a particle size distribution measuring device based on the electrical resistance method (Beckman Coulter, Multisizer 4) with an aperture size of 100 μm.
[0029] In this specification, the press molding bulk density means the density of a molded body formed by placing a sample in a circular mold frame with an inner diameter of 30 mm and pressing it at a specified pressure using a commercially available press. The press molding bulk density is a value that serves as an indicator of the bulk density of a powder layer when a thin layer of powder is formed using a roller or the like.
[0030] In this specification, the angle of repose is a value measured and calculated according to JIS R 9301-2-2: 1999 (Alumina powder - Part 2: Physical property measurement methods - 2: Angle of repose).
[0031] In this specification, the BET specific surface area is a value measured and calculated according to "6.2 Flow method (3.5) Single point method" of JIS R 1626:1996 (Determination of specific surface area of fine ceramic powder by gas adsorption BET method). As a pretreatment, the sample is heated to 180°C, nitrogen is flowed for 20 minutes, and then the measurement is performed using nitrogen as the adsorbent.
[0032] In this specification, the circularity is the average value of values calculated using the following formula (1) for 2000 or more particles, where the area of a projection image of particles obtained using an imaging particle size distribution analyzer is represented by S and the perimeter is represented by L.
[0033] 4πS / L 2 (1)
[0034] In this specification, the pressure loss of air permeation at a specified pressure is the pressure loss when air at room temperature (23°C) passes through the powder layer at a linear speed of 2 mm / sec, measured using a powder rheometer FT4 (Freeman Technology). Specifically, the sample is placed in a column with a column diameter of 25 mm and a column length of 20 mm, and the powder layer is pressurized at a specified pressure using a mesh piston. In addition, the powder loaded into the column is subjected to three downward conditioning operations before the measurement. The sample amount is set to 10 mL based on the adjusted volume.
[0035] <Inorganic Oxide Particles>
[0036] The D50 of the inorganic oxide particles is 5.5 to 9.0 μm, and the pressure loss for air permeation at a pressure of 12 kPa is 1.75 to 2.81 kPa. By satisfying the above range, a good balance between the flowability and bulk density of the powder material can be achieved.
[0037] The roundness of the inorganic oxide particles is preferably 0.90 or more. If the roundness is 0.90 or more, the friction between the particles is small, so good fluidity can be obtained. If the roundness is 0.90 or more, the filling property of the particles becomes high, so the compression molding volume density can be improved. From the same viewpoint, the roundness of the inorganic oxide particles is preferably 0.93 or more, more preferably 0.95 or more. The upper limit of the roundness of the inorganic oxide particles is not particularly limited, but can be set to 1.00 or 0.99, for example.
[0038] The pressure loss of the inorganic oxide particles for air permeation under a pressure of 12 kPa is 1.75 kPa or more, preferably 2.00 kPa or more, and more preferably 2.20 kPa or more. The pressure loss of the inorganic oxide particles for air permeation under a pressure of 12 kPa is 2.81 kPa or less, preferably 2.79 kPa or less, and more preferably 2.77 kPa or less. It is believed that if it is 1.75 kPa or more, a low shrinkage rate during sintering can be achieved. D50 is not too large, and the pressure loss for air permeation under a pressure of 12 kPa is 2.81 kPa or less. The inorganic oxide particles have a moderate volume density, and the binder easily enters between the powder materials.
[0039] The D50 of the inorganic oxide particles is 5.5 μm or more, preferably 6.0 μm or more, and more preferably 6.5 μm or more. The D50 of the inorganic oxide particles is 9.0 μm or less, preferably 8.5 μm or less, and more preferably 8.0 μm or less. If the D50 of the inorganic oxide particles is 5.5 μm or more, the filling property of the particles becomes higher, so the compacting volume density can be increased. If the D50 of the inorganic oxide particles is 5.5 μm or more, when the inorganic oxide particles are used as powder for stacking modeling, the shape stability of the powder layer formed is good, and the shrinkage rate during sintering can be reduced. If the D50 of the inorganic oxide particles is 9.0 μm or less, the filling property and fluidity of the particles can be within a range suitable for powder stacking modeling and coating applications.
[0040] The D10 of the inorganic oxide particles is preferably 1.0 to 4.0 μm, more preferably 2.0 to 3.8 μm, and further preferably 3.0 to 3.6 μm. If the D10 of the inorganic oxide particles is 1.0 μm or more, the filling property of the particles becomes higher, so the compacting volume density can be increased. If the D10 of the inorganic oxide particles is 1.0 μm or more, when the inorganic oxide particles are used as powder for stacking modeling, the shrinkage rate during sintering can be reduced. If the D10 of the inorganic oxide particles is 4.0 μm or less, the filling property and fluidity of the particles can be within a range suitable for powder stacking modeling and coating applications.
[0041] The D90 of the inorganic oxide particles is preferably 13.0 to 40.0 μm, more preferably 15.0 to 30.0 μm, and further preferably 21.0 to 25.0 μm. If the D90 of the inorganic oxide particles is 13.0 μm or more, the filling property of the particles becomes higher, so the compacting volume density can be increased. If the D90 of the inorganic oxide particles is 13.0 μm or more, when the inorganic oxide particles are used as a powder for stacking modeling, the shape stability of the powder layer formed is good. If the D90 of the inorganic oxide particles is 40.0 μm or less, the filling property and fluidity of the particles can be within a range suitable for powder stacking modeling and coating applications. If the D90 of the inorganic oxide particles is 40.0 μm or less, when the inorganic oxide particles are used as a powder for stacking modeling, the uniformity of the powder layer formed is better.
[0042] The volume ratio of particles with a particle size of 16.8 to 60.0 μm in the inorganic oxide particles is preferably 4.3% by volume or more, more preferably 10.0% by volume or more, and further preferably 15.0% by volume or more. The volume ratio of particles with a particle size of 16.8 to 60.0 μm in the inorganic oxide particles is preferably 33.5% by volume or less, more preferably 21.0% by volume or less, and further preferably 20.0% by volume or less. If the volume ratio of particles with a particle size of 16.8 to 60.0 μm is within the above range, it is possible to expect moderate fluidity when the inorganic oxide particles are used as powder for stacking modeling. The volume ratio of particles with a particle size of 16.8 to 60.0 μm in the inorganic oxide particles is a value determined by measuring the particle size distribution using a particle size distribution measuring device based on the resistance method (Beckman Coulter, Multisizer 4) with an aperture of 100 μm.
[0043] The volume ratio of particles with a particle size of 2.0 μm or more in the inorganic oxide particles is preferably 90.0 to 100 volume %, more preferably 93.0 to 100 volume %, and further preferably 95.0 to 100 volume %. If the volume ratio of particles with a particle size of 2.0 μm or more is 90.0 volume % or more, when the inorganic oxide particles are used as powder for laminated molding, the shrinkage rate during sintering can be reduced. The volume ratio of particles with a particle size of 2.0 μm or more in the inorganic oxide particles is a value determined using a laser diffraction-scattering particle size distribution measuring device (Michiko Baier Co., Ltd., MT3300EXII).
[0044] The ratio of D50 to D10 (D50 / D10) of the inorganic oxide particles is preferably 2.0 to 2.3. If D50 / D10 is within the above range, when the inorganic oxide particles are used in a binder spraying method, appropriate fluidity can be expected, and good laying properties that can form a uniform powder layer and shape stability that can maintain the shape during the period from the application of the binder to the sintering process can be achieved.
[0045] The ratio of D90 to D10 (D90 / D10) of the inorganic oxide particles is preferably 4.0 to 8.0, more preferably 5.0 to 7.5, and further preferably 5.5 to 7.0. If D90 / D10 is 8.0 or less, the particle size distribution of the inorganic oxide particles is within a certain range, so when used as a powder for stacking modeling, the fine particles are appropriately arranged between the coarse particles, and the fluidity can be appropriate. If D90 / D10 is 4.0 or more, when the inorganic oxide particles are used as a powder for stacking modeling, the fine particles are appropriately arranged between the coarse particles, and the volume density can be appropriate.
[0046] The ratio of D90 to D50 of the inorganic oxide particles (D90 / D50) is preferably 2.3 to 3.6, more preferably 2.5 to 3.5, and further preferably 2.8 to 3.4. If D90 / D50 is 3.6 or less, the particle size distribution of the inorganic oxide particles is within a certain range, so when used as a powder for stacking modeling, the fine particles are appropriately arranged between the coarse particles, and the fluidity can be appropriate. If D90 / D50 is 2.3 or more, when the inorganic oxide particles are used as a powder for stacking modeling, the fine particles are appropriately arranged between the coarse particles, and the volume density can be appropriate.
[0047] D10, D50, and D90 of the inorganic oxide particles preferably satisfy the relationship of the following formula (I).
[0048] (D10+D90) / D50≥2.7(I)
[0049] (D10+D90) / D50 is an index of the particle size distribution of the inorganic oxide particles, and the larger the value, the larger the particle size distribution width. When the value of (D10+D90) / D50 is 2.7 or more, that is, the inorganic oxide particles satisfy the relationship of formula (I), the particle size distribution width of the particles is moderately large. In this case, it is easy to become a moderate filling state in which the binder can enter between the powder materials. The value of (D10+D90) / D50 is more preferably 2.9 or more, and more preferably 3.0 or more. The value of (D10+D90) / D50 is preferably 6.0 or less, and more preferably 4.0 or less.
[0050] The angle of repose of the inorganic oxide particles is preferably 55 to 59°, more preferably 56 to 58°. The angle of repose is one of the indicators indicating the fluidity of the powder. If the angle of repose of the inorganic oxide particles is 55° or more, the shape stability of the powder layer formed by using the inorganic oxide particles as the powder for stacking modeling is good. If the angle of repose of the inorganic oxide particles is 59° or less, when the inorganic oxide particles are used in the powder stacking modeling method, the inorganic oxide particles can be smoothly supplied to the modeling table and evenly spread.
[0051] The BET specific surface area of the inorganic oxide particles is preferably 0.10 m 2 / g or more, more preferably 0.20m 2 / g or more, more preferably 0.30m 2 The BET specific surface area of the inorganic oxide particles is preferably 10.00 m 2 / g or less, more preferably 5.00m 2 / g or less, more preferably 2.00m 2 / g or less, particularly preferably 0.50m 2 The BET specific surface area of the inorganic oxide particles is preferably 0.10 to 10.00 m 2 / g, more preferably 0.10 to 5.00 m 2 / g, more preferably 0.20 to 2.00 m 2 / g, particularly preferably 0.30 to 0.50 m 2 / g. If the BET specific surface area is 0.10m 2 / g or more, the shape stability of the powder layer formed by using the inorganic oxide particles as the laminated modeling powder is good. 2 / g or less, when the inorganic oxide particles are used in a powder layering method, the inorganic oxide particles can be smoothly supplied to a modeling table and evenly spread.
[0052] The shape of the inorganic oxide particles is not particularly limited, and examples thereof include spherical, ellipsoidal, scaly, and amorphous shapes. Among them, spherical shapes are preferred in order to easily obtain an appropriate bulk density.
[0053] The inorganic oxide particles are preferably at least one selected from silica, alumina, zirconium oxide and titanium dioxide, more preferably alumina, and further preferably spherical alumina. Alumina has high thermal conductivity, melting point and hardness, is cheap, and is strong in acid and alkali resistance, so it is preferred from this point of view. The volume ratio of alumina in the inorganic oxide particles is preferably 50 volume % or more, more preferably 60 volume % or more, and further preferably 80 volume % or more. The upper limit of the volume ratio of alumina in the inorganic oxide particles is not particularly limited, and can be, for example, 100 volume %, 98 volume % or 95 volume %.
[0054] When the inorganic oxide particles are alumina, the bulk density of the inorganic oxide particles after press molding at a pressure of 98 MPa is preferably 2.45 to 2.54 g / cm 3 If the compacted volume density of the inorganic oxide particles at a pressure of 98 MPa is 2.45 g / cm 3 If the inorganic oxide particles are used as powder for laminated molding, the dimensional stability during sintering is good. If the compacting bulk density of the inorganic oxide particles at a pressure of 98 MPa is 2.54 g / cm 3 Next, when the inorganic oxide particles are used in the binder spraying method, the binder can easily enter between the powder materials when the binder is applied, and the strength of the molded body and the sintered body can be made sufficient.
[0055] Inorganic oxide particles can be used very suitably in powder layering molding methods. By using inorganic oxide particles, a molded body with few voids can be produced, and the effect of reducing the heat shrinkage during the sintering treatment of the molded body can be expected. In particular, since inorganic oxide particles have good laying properties and shape stability of the powder layer, as well as appropriate bulk density, they can be used very suitably in the binder injection method of spraying a liquid binder onto a fully spread powder material and curing it. Inorganic oxide particles can also be used in the powder bed fusion method of irradiating a powder bed covered with powder material with a laser or electron beam to selectively melt it for molding, as well as other powder layering molding methods.
[0056] Since the inorganic oxide particles have moderate fluidity and moderate bulk density that allows easy penetration of liquid, they can be used as filler materials that impart fluidity and thermal conductivity. Specifically, they can be used as fillers in heat dissipation materials, such as fillers in heat dissipation coatings, heat insulation coatings, and wear-resistant coatings that require good coating properties, fillers in heat conductive resin compositions having bonding properties, and fillers in heat conductive coating materials that have the function of curing in the atmosphere.
[0057] <Method for producing inorganic oxide particles>
[0058] Inorganic oxide particles can be manufactured, for example, by mixing a plurality of inorganic oxide particles having different particle size distributions so that the particle size distribution of the inorganic oxide particles is within a specified range. The particle size distribution of the inorganic oxide particles can also be adjusted by screening, etc. The particle size distribution of the inorganic oxide particles can be adjusted to an appropriate range by selecting the type and amount of the inorganic oxide particles to be matched. The mixing method of the materials is not particularly limited, and for example, a method of dry mixing or wet mixing of the materials can be cited. Mixing can be performed manually or using a blender.
[0059] As a more specific method for producing inorganic oxide particles, for example, a method of mixing the coarse inorganic oxide particles (A) shown below and the fine inorganic oxide particles (B) having a D50 smaller than the coarse inorganic oxide particles (A) can be cited. The coarse inorganic oxide particles (A) and the fine inorganic oxide particles (B) may be inorganic oxide particles of different types or inorganic oxide particles of the same type. If they are inorganic oxide particles of the same type, it is easy to mix and disperse the particles uniformly, so it is preferred.
[0060] [Coarse Inorganic Oxide Particles (A)]
[0061] The D50 of the coarse inorganic oxide particles (A) used is preferably 9.0 to 25.0 μm, more preferably 12.0 to 20.0 μm, and further preferably 14.0 to 18.0 μm. The D10 of the coarse inorganic oxide particles (A) is preferably 1.0 to 8.0 μm, more preferably 2.0 to 7.5 μm, and further preferably 3.0 to 7.0 μm. The D90 of the coarse inorganic oxide particles (A) is preferably 28.0 to 40.0 μm, more preferably 28.5 to 38.0 μm, and further preferably 29.0 to 36.0 μm.
[0062] The ratio of D50 to D10 (D50 / D10) of the coarse-grained inorganic oxide particles (A) is preferably 1.5 to 3.5, more preferably 1.7 to 3.2, and even more preferably 2.0 to 3.0. The ratio of D90 to D10 (D90 / D10) of the coarse-grained inorganic oxide particles (A) is preferably 3.5 to 9.0, more preferably 4.0 to 7.0, and even more preferably 4.5 to 6.0. The ratio of D90 to D50 (D90 / D50) of the coarse-grained inorganic oxide particles (A) is preferably 1.7 to 2.3, more preferably 1.8 to 2.2, and even more preferably 1.9 to 2.0.
[0063] The shape of the coarse inorganic oxide particles (A) is not particularly limited, and examples thereof include spherical, ellipsoidal, scaly, and amorphous shapes. Among them, spherical shapes are preferred in order to easily obtain an appropriate bulk density.
[0064] The coarse-grained inorganic oxide particles (A) are preferably at least one selected from silica, alumina, zirconium oxide and titania, more preferably alumina, and further preferably spherical alumina. The volume ratio of alumina in the coarse-grained inorganic oxide particles (A) is preferably 50% by volume or more, more preferably 60% by volume or more, and further preferably 80% by volume or more. The upper limit of the volume ratio of alumina in the coarse-grained inorganic oxide particles (A) is not particularly limited, and can be, for example, 100% by volume, 98% by volume or 95% by volume.
[0065] [Fine Inorganic Oxide Particles (B)]
[0066] The D50 of the fine-particle inorganic oxide particles (B) is smaller than the D50 of the coarse-particle inorganic oxide particles (A). The D50 of the fine-particle inorganic oxide particles (B) used is preferably 5.0 to 8.0 μm, more preferably 5.5 to 7.8 μm, and further preferably 6.0 to 7.5 μm. The D10 of the fine-particle inorganic oxide particles (B) is preferably 1.0 to 4.0 μm, more preferably 2.0 to 3.8 μm, and further preferably 2.5 to 3.5 μm. The D90 of the fine-particle inorganic oxide particles (B) is preferably 9.0 to 25.0 μm, more preferably 12.0 to 24.0 μm, and further preferably 14.0 to 23.0 μm.
[0067] The ratio of D50 to D10 (D50 / D10) of the fine-particle inorganic oxide particles (B) is preferably 1.5 to 5.0, more preferably 1.7 to 4.0, and even more preferably 1.8 to 3.0. The ratio of D90 to D10 (D90 / D10) of the fine-particle inorganic oxide particles (B) is preferably 3.5 to 9.0, more preferably 4.5 to 8.0, and even more preferably 5.5 to 7.0. The ratio of D90 to D50 (D90 / D50) of the fine-particle inorganic oxide particles (B) is preferably 2.5 to 3.5, more preferably 2.7 to 3.2, and even more preferably 2.9 to 3.1.
[0068] The shape of the fine inorganic oxide particles (B) is not particularly limited, and examples thereof include spherical, ellipsoidal, scaly, and amorphous shapes. Among them, spherical shapes are preferred in order to easily obtain an appropriate bulk density.
[0069] The fine inorganic oxide particles (B) are preferably at least one selected from silica, alumina, zirconium oxide and titanium dioxide, more preferably alumina, and further preferably spherical alumina. The volume ratio of alumina in the fine inorganic oxide particles (B) is preferably 50% by volume or more, more preferably 60% by volume or more, and further preferably 80% by volume or more. The upper limit of the volume ratio of alumina in the fine inorganic oxide particles (B) is not particularly limited, and can be, for example, 100% by volume, 98% by volume or 95% by volume.
[0070] The volume ratio of the coarse inorganic oxide particles (A) relative to the total volume of the coarse inorganic oxide particles (A) and the fine inorganic oxide particles (B) before mixing is selected so that the particle size distribution of the inorganic oxide particles is within an appropriate range, and can be set to, for example, 9.5 to 29.0 volume %.
[0071] <Method for producing a three-dimensional laminated structure>
[0072] The three-dimensional stacked body can be manufactured by processing inorganic oxide particles using a known powder stacking method. Examples of the powder stacking method include a binder jet method and a powder bed fusion method. The powder stacking method using inorganic oxide particles as a stacking powder generally includes the following steps.
[0073] (1) a step of supplying inorganic oxide particles to a molding table of a powder layer molding device;
[0074] (2) a step of uniformly and thinly spreading the supplied inorganic oxide particles using a roller or the like to form a thin layer of the inorganic oxide particles;
[0075] (3) a step of irradiating the formed thin layer of inorganic oxide particles with laser light or electron beams, or applying a liquid containing a binder to bond the inorganic oxide particles;
[0076] (4) A step of supplying new inorganic oxide particles onto the solidified inorganic oxide particles.
[0077] Then, by repeating steps (2) to (4), a target three-dimensional layered structure can be manufactured.
[0078] As a method for applying a liquid containing an adhesive, a method for discharging a liquid containing an adhesive is preferred. There are no particular restrictions on the method for discharging a liquid containing an adhesive, and examples thereof include a dispenser method, a spray method, and an inkjet method. Among them, the inkjet method is preferred because the quantitative properties of the droplets are good and a large area can be coated.
[0079] When using an inkjet method, the liquid containing the adhesive can be applied using an inkjet head having a nozzle for discharging the liquid. As the inkjet head, an inkjet head in a known inkjet printer can be used very suitably, for example, the industrial inkjet RICOH MH / GH series (Ricoh Co., Ltd.) can be cited.
[0080] The binder is not particularly limited, and known binders such as polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, polyvinyl butyral, acrylic resin, and polyamide can be used. The viscosity of the binder can be adjusted using an appropriate solvent.
[0081] <Method for producing sintered body>
[0082] The sintered body can be produced by sintering the three-dimensional stacked body using a known sintering method. It is preferred that a degreasing treatment be performed before the sintering treatment. A specific method for producing the sintered body is exemplified below.
[0083] The three-dimensional stacked body is placed in a sintering furnace, and the temperature in the furnace is raised to a degreasing treatment temperature. The degreasing treatment temperature can be appropriately set within the range of 500 to 700°C, for example. Thereafter, the temperature in the furnace is maintained at the degreasing treatment temperature for 0.5 to 4 hours to perform a degreasing treatment to burn the organic components. The degreasing treatment is performed in an air atmosphere. The degreasing time can be set according to the type of binder and the ratio of organic components in the three-dimensional stacked body. Next, the temperature in the furnace is raised to a sintering treatment temperature. The sintering treatment temperature can be appropriately set within the range of 900 to 1300°C, for example. Thereafter, the temperature in the furnace is maintained at the sintering treatment temperature for 1 to 7 hours to perform a sintering treatment to sinter the three-dimensional stacked body, thereby obtaining a sintered body. The sintering temperature and sintering time can be set according to the type of inorganic oxide powder. The sintering treatment can be performed in an inert gas atmosphere or in an air atmosphere.
[0084] Example
[0085] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0086] <Materials used>
[0087] Coarse inorganic oxide particles (A): spherical alumina (Alnabis (trademark) / CB, Risenno Corporation): true density 3.95 g / m 3
[0088] Coarse inorganic oxide particles (B): spherical alumina (Alnabis (trademark) / CB, Risenno Corporation): true density 3.95 g / m 3
[0089] <Evaluation method>
[0090] (Volume Density)
[0091] The bulk density is evaluated by using the compression molding bulk density under a pressure of 98 MPa. Specifically, a sample is placed in a circular mold frame with an inner diameter of 30 mm, and a molded body is produced under a pressure of 98 MPa using a commercially available press. The density of the resulting molded body is determined as the compression molding bulk density under a pressure of 98 MPa. If the compression molding bulk density is 2.45 g / cm 3 If the above-mentioned compacting bulk density is 2.54 g / cm 3 The following is an example of an excellent binder application in a binder jetting method, where the binder can penetrate between the powder materials. That is, the bulk density of the compact is 2.45 to 2.54 g / cm 3 In the case of , the bulk density was evaluated to be good.
[0092] (Roundness)
[0093] The area S and the perimeter L were measured using FPIA-3000 (Malvern Panalytical). As a pre-treatment, due to the measurement range of the device, about 10 g of the sample was placed in a metal sieve with a diameter of 200 mm and a mesh size of 25 μm, and particles larger than 25 μm were removed with spray water. The sample under the sieve was transferred to a plastic container as a measurement sample. The measurement conditions were set to LPF / HPF standard (20x lens) and bright field, and particle sheath reagent (Malvern Panalytical) was used as the measurement solvent. 2 g of the sample was weighed and placed in a 50 mL beaker in such a way that the number of effective particles was more than 2000 and the number of effective particles / total number of particles was 55-70%. 50 mL of pure water was added, and after being dispersed for 3 minutes with a 200 W ultrasonic disperser, it was put into the device for measurement. As data processing after the measurement, the data when there were multiple particles on one screen was deleted, and the roundness was calculated.
[0094] (Liquidity)
[0095] The fluidity is evaluated by the angle of repose. If the angle of repose is 55° or more, when the inorganic oxide particles are used in the binder spraying method, the shape can be maintained from the application of the binder to the sintering process, and from this point of view, the shape stability is excellent. If it is 59° or less, when the inorganic oxide particles are used in the binder spraying method, the inorganic oxide particles can be smoothly supplied to the molding table and evenly spread, and from this point of view, the laying property is excellent. That is, when the angle of repose is 55 to 59°, from the viewpoint of the balance between shape stability and laying property, the fluidity is evaluated to be good.
[0096] (Pressure loss due to air permeation)
[0097] The pressure loss due to air permeation was measured at a pressure of 12 kPa.
[0098] [Example 1]
[0099] Using a rocking mixer (RMC-600(S) / LH, Aichi Electric Co., Ltd.), coarse inorganic oxide particles (A) and fine inorganic oxide particles (B) having the particle sizes and particle size ratios shown in Table 1 were mixed at a ratio such that the volume ratio of the coarse inorganic oxide particles (A) relative to the total volume of the coarse inorganic oxide particles (A) and the fine inorganic oxide particles (B) before mixing was 11.1 volume %, thereby obtaining inorganic oxide particles. Table 1 also shows the particle size volume ratio calculated by the following formula (2).
[0100] (Volume ratio of coarse inorganic oxide particles (A)×D50 of coarse inorganic oxide particles (A)) / (Volume ratio of fine inorganic oxide particles (B)×D50 of fine inorganic oxide particles (B)) (2)
[0101] The particle size distribution, BET specific surface area, circularity, fluidity, pressure loss due to air permeation, and press-molded bulk density of the obtained inorganic oxide particles were evaluated.
[0102] [Examples 2 to 4, Comparative Examples 1 to 3]
[0103] The inorganic oxide particles were obtained in the same manner as in Example 1 except that the volume ratio of the coarse-grained inorganic oxide particles (A) to the volume of the coarse-grained inorganic oxide particles (A) and the fine-grained inorganic oxide particles (B) before mixing was set as shown in Table 1. Table 1 also records the particle size volume ratio calculated by the above formula (2). The particle size distribution, BET specific surface area, roundness, fluidity, pressure loss for air permeation, and press-molded bulk density of the obtained inorganic oxide particles were evaluated. The results are shown in Table 2. In addition, those not evaluated are recorded as "-".
[0104]
[0105]
[0106]
[0107] As shown in Examples 1 to 4 and Comparative Examples 1 to 3, the inorganic oxide particles having a D50 of 5.5 to 9.0 μm and a pressure loss of 1.75 to 2.81 kPa for air permeation at a pressure of 12 kPa have good bulk density and fluidity. Examples 1 to 4 have an angle of repose in the range of 55 to 59° and have moderate fluidity for the binder spraying method. Therefore, it is believed that when Examples 1 to 4 are used in the binder spraying method, a uniform powder layer can be formed when a thin layer is formed, and the shape can be maintained from the application of the binder to the sintering process. In addition, Examples 1 to 4 have a press-molded bulk density of 2.45 to 2.54 g / cm 3 Therefore, it is considered that when Examples 1 to 4 are used in the binder spraying method, the binder can enter between the powder materials and a low shrinkage rate during sintering can be achieved.
[0108] Comparative Example 1 has a low compacting bulk density. It is presumed that this is because the adhesion between particles is high due to the small D50, and air easily enters during compacting. As a result, it is expected that Comparative Example 1 will have a large shrinkage rate during sintering when used in the binder jetting method. Comparative Example 2 has a larger D50 than Comparative Example 1, so it is expected that the adhesion between particles is lower than that of Comparative Example 1, and the amount of air entering during compacting is small. In addition to the small amount of air entering, Comparative Example 2 has a high pressure loss for air permeation under a pressure of 12 kPa, so it is a material that is easy to fill with high density. Such a material has a large compacting bulk density, and it is difficult for the binder to enter between particles. Therefore, it is expected that it is difficult to obtain the desired shape when used in the binder jetting method. Comparative Example 3 is a material with a large D50 and low adhesion between particles. The pressure loss for air permeation under a pressure of 12 kPa is low, which also shows that the adhesion between particles of Comparative Example 3 is low. Such a material has a small repose angle as a fluidity index, and it is expected that it is difficult to form a uniform powder layer when forming a thin layer of powder for stacking molding. Materials with large D50 and low pressure loss for air permeation at a pressure of 12 kPa are estimated to be materials that are easy to block gaps in the powder by pressing. Such materials have high bulk density after pressing and it is difficult for the binder to enter between particles. Therefore, it is expected that it is difficult to obtain a desired shape when used in the binder spraying method.
Claims
1. An inorganic oxide particle, D50 is 5.5~9.0μm, The pressure loss for air permeation at a pressure of 12 kPa is 1.75 to 2.81 kPa. 2 . The inorganic oxide particles according to claim 1 , wherein (D10+D90) / D50 is 2.7 or more.
3. The inorganic oxide particles according to claim 1, wherein the BET specific surface area is 0.10 to 10.00 m 2 / g. 4 . The inorganic oxide particles according to claim 1 , wherein the volume ratio of particles having a particle size of 16.8 to 60.0 μm is 4.3 to 33.5% by volume. 5 . The inorganic oxide particles according to claim 1 , wherein the volume ratio of particles having a particle size of 2.0 μm or more is 90.0% by volume or more. The inorganic oxide particles according to any one of claims 1 to 3, which are aluminum oxide. 7 . The inorganic oxide particles according to claim 1 , having a circularity of 0.90 or more. 8 . The inorganic oxide particles according to claim 1 , which are used in a powder layering method.
9. The inorganic oxide particles according to claim 6, wherein the compacted bulk density at a pressure of 98 MPa is 2.45 to 2.54 g / cm 3 . 10 . A sintered body, which is a sintered body of the inorganic oxide particles according to claim 1 . 11 . A method for producing a three-dimensional layered structure by binder spraying, comprising: applying a liquid containing a binder to the inorganic oxide particles according to claim 1 to form a three-dimensional layered structure.
12. A method for producing a sintered body, comprising: Forming a three-dimensional stacked body by applying a liquid containing a binder to the inorganic oxide particles according to any one of claims 1 to 3; and The three-dimensional stacked shaped body is sintered.
Citation Information
Patent Citations
Three dimensional printing of cermet or cemented carbide
CN108883467A
Production of photocurable formulation for additive manufacturing
CN109311759A
Method for manufacturing three-dimensional molded object, apparatus for manufacturing three-dimensional molded object, and three-dimensional molded object
JP2016182697A
Powder for lamination molding
JP2018130835A
Techniques for controlling build material flow characteristics in additive manufacturing and related systems and methods
US20220250149A1